Perceptions of Students on Differentiated Learning of Video Content in Long Multiplication Mathematics Lessons - Asnaini, Desi (PPSDP International Journal of Education, 2025)
Currently, students often feel bored with the teaching and learning activities in the classroom, especially in Mathematics learning, for that a learning style approach is needed that is adjusted to the needs of each student. The purpose of studying content differentiation through videos for elementary school children is to provide a more meaningful learning experience and in accordance with the needs and learning styles of each student, facilitate diverse learning styles and provide an interactive learning experience. By using visual and auditory content videos, learning for grade 3 elementary school children greatly helps students understand the material to be studied; after watching the video, the teacher can interact directly with students through questions or quizzes based on the learning videos that have been watched by students. The method used in this study is qualitative, where this approach focuses on an in-depth understanding of socio-cultural phenomena and human behavior through non-numerical data. Qualitative research emphasizes the context of the process and quality rather than measurement. In this study, video content differentiation is a strategy where creators and content providers provide a variety of learning styles to students.